Bantal Menyusui Memengaruhi Motivasi, Produksi ASI, dan Musculoskeletal Disorder pada Ibu Menyusui - Asih, Yusari (Poltekkes Kemenkes Tanjung Karang, 2021)
Breastfeeding in a sitting position for 30 minutes with the mother's hand supporting the baby causes maternal fatigue. One way to increase motivation, breast milk production and reduce musculoskeletal disorder is by using a breastfeeding pillow. The purpose of this study was to determine the effect of using a breastfeeding pillow on motivation, milk production, and musculoskeletal disorder of breastfeeding mothers in the Pringsewu Regency in 2020. This study is a quasi-research. experiment with post-test design with control group design. The sampling technique was purposive sampling, the number of samples was 48 breastfeeding mothers 0-1 months. The intervention group used a redesigned breastfeeding pillow, the control group used a regular breastfeeding pillow. The data were processed with univariate (mean) and bivariate analysis with Independent T-Test and Hotelling T-Test. The results showed that on average the respondents had the motivation to breastfeed in the high category, breast milk production in the good category, and musculoskeletal disorder in the not sick category. There were significant differences in motivation for breastfeeding, milk production, and musculoskeletal disorders between the group of mothers who used the redesigned breastfeeding pillow and the group that used the regular breastfeeding pillow. To midwives to promote the use of redesigned breastfeeding pillows to help increase motivation, milk production, and breastfeeding comfort so that musculoskeletal disorders do not occur and researchers can conduct further research with other variables that can affect motivation, milk production, and musculoskeletal disorders in breastfeeding mothers.